2007
DOI: 10.1021/ma062322e
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Supramolecular Assemblies Based on Hyaluronic Acid Derivatives Bearing Bivalent β-Cyclodextrin and Adamantane Moieties

Abstract: New supramolecular assemblies based on hyaluronic acid stabilized by divalent -cyclodextrin/ adamantane ( -CD/AD) complexes were synthesized with the aim to compare their viscoelastic behavior in aqueous medium with systems resulting from monovalent complexes. For this purpose, dimers of AD and -CD to be coupled to hyaluronic acid were prepared by multistep chemical synthetic pathways. Investigation of the complexation properties of these dimers by isothermal titration calorimetry (ITC) experiments revealed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
63
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 29 publications
8
63
0
Order By: Relevance
“…On average, more than 90% of monomeric PTX/CD complexes dissociated after 100 ns, whereas PTX/pCD and pPTX/pCD displayed only 20-30% PTX/CD pair dissociations after the same time. These data support the conclusion that the stability of the nanoassembly results from the multiplicity of the PTX/CD inclusion complexes formed between the two polymer conjugates 32,33 .…”
Section: Molecular Dynamic Simulationsupporting
confidence: 85%
“…On average, more than 90% of monomeric PTX/CD complexes dissociated after 100 ns, whereas PTX/pCD and pPTX/pCD displayed only 20-30% PTX/CD pair dissociations after the same time. These data support the conclusion that the stability of the nanoassembly results from the multiplicity of the PTX/CD inclusion complexes formed between the two polymer conjugates 32,33 .…”
Section: Molecular Dynamic Simulationsupporting
confidence: 85%
“…[12][13][14][15] A great variety of physically crosslinked hydrogels have been reported, which are based on ionic interactions, [16,17] hydrophobic interactions, [18][19][20] hydrogen bonds, [21,22] crystallinity, [23] stereocomplex formation, [24][25][26][27] or specific biomimetic interactions. [28][29][30] We and others recently reported on selfassembling hydrogel systems, [31][32][33][34][35][36][37] in which physical crosslinking is established by inclusion complex formation between b-cyclodextrin (bCD) and a complementary low molecular weight guest molecule. The cyclic oligosaccharide bCD is composed of 7 glucopyranose units that are joined by a-1,4-glucosidic linkages.…”
Section: Introductionmentioning
confidence: 99%
“…[38] Driven by hydrophobic and van der Waals interactions, the relatively hydrophobic pocket of bCD serves as a reversible binding site for a wide range of lipophilic molecules (e.g., adamantane and cholesterol). [39][40][41] Reversible hydrogel systems, for example, those composed of adamantane-and bCD-grafted chitosan [42] or hyaluronic acid [33,43] have been described in the literature. Also, stimuli-responsive gels were formed after combining poly(acrylamide) derivatized with either bCD or aromatic guest molecules.…”
Section: Introductionmentioning
confidence: 99%
“…As model system, a mixture of two hyaluronic acid derivatives functionalized either with bCD or adamantly residues was chosen [29,65]. Above the overlap concentration it was found that these polymer systems generate parallel strands of contrarily derivatized polymers, denoted as railway complexes.…”
Section: Structure-property Relationship Of Polymers Containing Cyclomentioning
confidence: 99%